(untitled) (Swiss Medical Weekly, 2010)
BACKGROUND: Hospitalised patients with acute heart failure (AHF) suffer from a high morbidity and mortality, which might, at least partly, be influenced by concomitant infections. The aim of this observational study was to investigate the impact of infections on the clinical course of critically ill patients with AHF, both present on intensive care unit (ICU) admission and acquired during the ICU stay. METHODS: From 178 consecutive AHF patients, 76 were treated medically and 21 required emergency cardiac surgery. The remaining 81 patients, who underwent elective cardiac surgery, were excluded from the assessment of infections on ICU admission, but were included in the analysis of nosocomial infections during the ICU stay. RESULTS: A total of 16% of patients (16/97) had infections on ICU admission. These patients had longer ICU (6 vs. 3 days, p = 0.04) and hospital (19 vs. 11 days, p = 0.04) stays than patients without infections. Although not statistically significant, there was a trend for increased mortality at 30 days (44% vs. 24%, p = 0.13) and 6 months (57% vs. 31%, p = 0.13) in AHF patients with infections on ICU admission. Infection complications during the ICU stay occurred in 17% (30/178) of AHF patients and significantly increased their mortality at 30 days (33% vs. 14%, p = 0.02) and 6 months (41% vs. 18%, p = 0.02). CONCLUSIONS: In this observational study, infections present on ICU admission or occurring during the ICU stay had a negative impact on the morbidity and mortality of critically ill patients with AHF. Future studies are needed to gain a better understanding of the interactions between heart failure and infections, as a better knowledge of this field may have an important therapeutic potential.